Pengaruh Penerapan Literasi Digital Terhadap Peningkatan Pengetahuan Dalam Pembelajaran Peserta Didik Di SMK Madinatul Hadid Cilegon - Ahmad Sayuri; Desty Endrawati Subroto; Mohamad Bayi Tabrani (Journal Innovation In Education, 2023)
This study is motivated by the low use of digital literacy and lack of knowledge in learning, so the researcher aims to find out how much influence the application of digital literacy has on increasing students' knowledge at SMK Madinatul Hadid Cilegon.. This research uses quantitative methods. Quantitative method is a method for testing certain theories by examining the relationship between variables. Variables are measured usually using research instruments so that data consisting of numbers can be analyzed based on statistical procedures. Research results obtained based on 57 respondents' answers with the score (2,565: 3,135) x 100% = 81.82% of the expected criteria. It can be concluded that the application of digital literacy (X) is in the medium category. While increasing knowledge in learning (Y) with a score of (2,601: 3,135) x 100% = 82.97% of the expected criteria. It can be concluded that increasing knowledge in student learning at SMK Madinatul Hadid Cilegon is in the good category.